Rural architectural heritage conservation and sustainability in Turkey: The case of karaca village of malatya region - Ol?un, Tuba Nur; Karatosun, Müjgan Bahtiyar (WITPress, 2019)
The rural architectural heritage has become a field of study in which many studies have been carried out and the importance of which has been recognized in the world in recent years. The rural areas, which are unique in their physical and social sense with their unique characteristics, are unique in their architectural terms. In this context, conserving the architectural heritage in rural areas and making these areas sustainable have great importance. Rural architectural heritage conservation is an issue discussed in Turkey as in many countries around the world. However, the developments seen in this area in Turkey, considered a fairly new compared with developments in the world. Thus, when looking at studies in Turkey, for the conservation of the rural architectural heritage, it is seen that there are many studies in literature and practice in some rural areas. But, there are no studies on that heritage in some areas. There are many parameters that characterize the rural architectural heritage. One of these parameters is the building material. Considering the rural architectural heritage in Turkey, especially building materials according to geography and climate conditions, it is observed that the shape of use. In this context, natural materials such as stone, wood and earthen are common in rural areas. In particular, the earthen material used by conventional techniques is not long lasting; the widespread use of these materials causes rapid destruction of architectural elements. In this sense, it has great importance to accelerate the efforts for the conservation of the architectural heritage built with earthen material and to implement the practices as soon as possible. In Turkey, one of four in rural architectural heritage built with earthen material located in the most intense region is Malatya. Karaca Village, which is located in the east of the Malatya, is a very striking example with its qualities. However, there are no studies on this and many other examples. In this context, the aim of the study; in Turkey, especially earthen material should attract attention to rural architectural heritage and to contribute to the preservation of this heritage. In the study, as first, the conservation of the rural architectural heritage in the world and Turkey and will be examined for the sustainability process; then, the rapidly losing areas of earthen material will be emphasized. Thus, in this sense stands out in Turkey, Malatya, located in the village of Karaca will be elaborated. As a result of the study, both in the world, in both Turkey; to discuss the current status of the rural architectural heritage built with earthen material; it is aimed to contribute to the preservation and sustainability of this heritage. © 2019 WIT Press.
Keywords: Conservation; Earthen; Malatya; Rural architecture heritage; Sustainability